Contemporary Nutrition : - Wardlaw, Gordon M. (McGraw-Hill, 2003)
For students who lack a strong science background, Contemporary Nutrition provides the ideal balance of reliable nutrition information and practical consumer-oriented knowledge. With his friendly writing style, Gordon Wardlaw acts as the student's personal guide to dispelling common misconceptions and to gaining a solid foundation for making informed nutrition choices. --This text refers to an out of print or unavailable edition of this title.